Consumer acceptance of low-dose irradiated, boneless, pork chops - Luchsinger, S.E.; Garcia Zepeda, C.M.; Chambers, Edgar, IV; Hollingsworth, M.E.; Hunt, Melvin C.; Marsden, James L.; Stroda, Sally L.; Rubio Canas, E.J.; Kastner, Curtis L.; Kuecker, W.G.; Mata, T.; Kropf, Donald H. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Acceptance of irradiated, chilled, boneless, pork chops and nonirradiated controls by consumers was not different. Coupled with consumer concerns about food safety and well-documented improvement in consumer attitudes about irradiated foods, the potential for market acceptance is very promising.
Keywords: Swine; Irradiation; Consumer acceptance